Recent studies of car disc brake squeal - Abu Bakar, Abd. Rahim; Ouyang, Huajiang (Nova Science Publishers, Inc, 2008)
Friction-induced vibration and noise emanating from car disc brakes is a source of considerable discomfort and leads to customer dissatisfaction. The high frequency noise above 1 kHz, known as squeal, is very annoying and very difficult to eliminate. There are typically two methods available to study car disc brake squeal, namely complex eigenvalue analysis and dynamic transient analysis. Although complex eigenvalue analysis is the standard methodology used in the brake research community, transient analysis is gradually gaining popularity. In contrast with complex eigenvalues analysis for assessing only the stability of a system, transient analysis is capable of determining the vibration level and in theory may cover the influence of the temperature distribution due to heat transfer between brake components and into the environment, and other time-variant physical processes, and nonlinearities. Wear is another distinct aspect of a brake system that influences squeal generation and itself is affected by the surface roughness of the components in sliding contact. This chapter reports recent research into car disc brake squeal conducted at the University of Liverpool. The detailed and refined finite element model of a real disc brake considers the surface roughness of brake pads and allows the investigation into the contact pressure distribution affected by the surface roughness and wear. It also includes transient analysis of heat transfer and its influence on the contact pressure distribution. Finally transient analysis of the vibration of the brake with the thermal effect is presented. These studies represent recent advances in the numerical studies of car brake squeal.